Leprosy in Brazil: From the social developments to the diagnosis-therapeutic evolution of the disease - Costa, Arthur Kennedy Martins; Silva, Dener Cleiton Souza e; Rosa, Paulo Henrique da Rocha; Gonçalves, Roberani Borges Vaz; Santos, Vinícius Oliveira; Guimarães, Yasmin Parreira; Carneiro , Viviane Santos Mendes (Seven Editora, 2024)
Few pathologies have marked the course of history as much as leprosy, in view of their geographical distribution, the level of contagion and the degree of involvement in the organism of the infected individual. To gather information on the epidemiology, origin and management of leprosy, this paper outlines an analysis of other bibliographies that have extensive relevance on this disease, including its biopsychosocial impacts on the patient's life. This is a bibliographic review in which works published in the last eight years were selected, with the aim of analyzing and disseminating the information captured. The results showed that the diagnosis of leprosy is based on clinical and epidemiological criteria, in addition to specific histological evaluation and sputum smear microscopy, emphasizing the importance of skin and serological tests. It is observed that the current treatment protocol consists of the use of drugs that cure the disease, with remission rates of up to 98%. Thus, the objective of this study is to identify the evidence available in the scientific literature about the main clinical manifestations of leprosy, the pathogenic mechanisms of the bacilli, as well as the methods of early diagnosis based on clinical and laboratory analyses and their therapeutic modalities. Despite the relevant considerations of the diagnosis-treatment dyad, Brazil is among the countries with the most registered cases, still placing this disease as a major public health problem, which confirms the continuous fight against the bacillary disease. DOI:https://doi.org/10.56238/sevened2024.001-058